Performance of self-compacting concrete containing recycled coarse aggregate. - Alsaadi Alsaidi; Yahya , Mohamed; Ibrahim Gargar (Sebha University Conference Proceedings, 2025)
This study aims to evaluate the performance of self-compacting concrete when replacing natural coarse aggregate with recycled aggregate at varying ratios (20%, 40%, 60%, 80%, and 100%), in the context of promoting sustainability in the construction sector and reducing dependence on natural resources. Natural aggregate from the Jufrah region in Libya was used as the primary source, while the recycled aggregate was obtained from crushed concrete, addressing the issue of waste disposal from demolished buildings. The compressive strength of the mixes was measured at different ages (3, 7, 21, 28, and 60 days). The results showed that the fresh properties of the mixes remained within EFNARC standards. Moreover, replacing 20% of natural aggregate with recycled aggregate resulted in a 6% reduction in compressive strength at 3 days and 15% at 28 days, while a 40% replacement led to a 10% reduction at 3 days and 25% at 28 days. These findings indicate that the use of recycled aggregate negatively affects compressive strength, especially at higher replacement levels. However, it can still be successfully used in specific applications within well-defined limits, contributing to environmental goals without significantly compromising concrete performance.